2010
DOI: 10.1016/j.ijrobp.2010.07.340
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Induced Rib Fractures after Hypofractionated Stereotactic Body Radiation Therapy: The Risk Factors and Dose-Volume Relationship

Abstract: Results: With the1 min. irradiation, the neutron yield from brass is about a factor of 3 lower than that of W, and the decay of activities is about 10 times faster. For the second simulation, the neutron activity builds up slowly in brass, from about 7x10 3 Bq/cm 3 at the end of week one to a maximum of 10 4 Bq/cm 3 at the end of week 7. For W, the neutron activity builds up slowly from about 5.5x10 6 Bq/cm 3 at the end of week one, to about 9x10 6 Bq/cm 3 (0.24 mCi) at the end of week 5. The neutron activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 0 publications
3
28
2
Order By: Relevance
“…In our study, grade 2 RFs occurred in 12 patients following PBT (19.4%), with a three-year cumulative incidence rate of 30.2%. With regard to SRT, several groups reported RFs frequencies ranging from 4% to 37.7% after SRT for earlystage NSCLC; these rates were not much higher compared with those observed in our study (30.2%) (Pettersson et al 2009;Dunlap et al 2010;Andolino et al 2011;Welsh et al 2011;Asai et al 2012;Creach et al 2012;Mutter et al 2012;Stephans et al 2012;Taremi et al 2012;Nambu et al 2013). Although PBT reportedly offers advantages over SRT, it has not been reported to dramatically reduce RFs incidence (Georg et al 2008;Kadoya et al 2011).…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…In our study, grade 2 RFs occurred in 12 patients following PBT (19.4%), with a three-year cumulative incidence rate of 30.2%. With regard to SRT, several groups reported RFs frequencies ranging from 4% to 37.7% after SRT for earlystage NSCLC; these rates were not much higher compared with those observed in our study (30.2%) (Pettersson et al 2009;Dunlap et al 2010;Andolino et al 2011;Welsh et al 2011;Asai et al 2012;Creach et al 2012;Mutter et al 2012;Stephans et al 2012;Taremi et al 2012;Nambu et al 2013). Although PBT reportedly offers advantages over SRT, it has not been reported to dramatically reduce RFs incidence (Georg et al 2008;Kadoya et al 2011).…”
Section: Discussioncontrasting
confidence: 71%
“…In that study, BEDs for 50 and 65 Gy calculated with α/β = 3 Gy were 83 and 108 Gy 3 (RBE), respectively; these values were lower than our results for V120 with PBT. Using ROC curves for dosimetric parameters with SRT, Asai et al (2012) evaluated doses administered to 374 ribs and reported a 3-year fracture rate of 37.7%. Further, they reported that D max , V40, V30, and V20 were significantly higher in fractured ribs than in nonfractured ribs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chest wall toxicity was significantly related to dose-volume parameters 9,10) and in our study, V30 Gy and V32 Gy of the chest wall were significantly reduced in the adaptive plan. Bhatt et al 14) reported that the doses of the chest wall and left ventricle were reduced in adaptive plans compared with initial plans.…”
Section: Discussionsupporting
confidence: 59%
“…[3][4][5] Several studies reported that higher biologically equivalent dose was related to improved local control and survival. 6,7) However, large fraction size may increase the toxicities of organs at risk (OARs), including the lung, 8) chest wall 9,10) and large bronchus. 11) Therefore, a smaller margin around the tumor is warranted in order to reduce radiation-induced normal tissue toxicities.…”
Section: Introductionmentioning
confidence: 99%